2020
DOI: 10.46328/ijemst.v8i2.843
|View full text |Cite
|
Sign up to set email alerts
|

The Use of History of Mathematics in the Mathematics Classroom: An Action Study

Abstract: In this action study, instructional environments were enriched with activities related to the history of mathematics in order to deepen students’ beliefs about mathematics and reveal for them fun, interesting, and useful activities. The study enrolled twenty-four 8th-grade students. Data were collected by using multiple data collection tools. The data regarding the students’ beliefs about mathematics were collected via written opinion forms and semi-structured interviews. Prior to the study, the students perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…Students also have the opportunity to discover different methods to solve mathematical problems (Goktepe & Ozdemir, 2013). In addition, practising activities related to HoM in class can develop a fun and interesting learning experience for the students and deepen their beliefs towards Mathematics ( Bütüner & Baki, 2020). This is supported by Ozdemir et al (2012) in their study who have found that HoM helps to strengthen students' geometric proof skills besides attracting their interest in terms of learning the topic.…”
Section: Implementation Of Hom In Teaching and Learning Mathematicsmentioning
confidence: 95%
See 1 more Smart Citation
“…Students also have the opportunity to discover different methods to solve mathematical problems (Goktepe & Ozdemir, 2013). In addition, practising activities related to HoM in class can develop a fun and interesting learning experience for the students and deepen their beliefs towards Mathematics ( Bütüner & Baki, 2020). This is supported by Ozdemir et al (2012) in their study who have found that HoM helps to strengthen students' geometric proof skills besides attracting their interest in terms of learning the topic.…”
Section: Implementation Of Hom In Teaching and Learning Mathematicsmentioning
confidence: 95%
“…HoM can also help students to understand the origins of a topic in Mathematics in addition to helping them to relate what they have learned in Mathematics to their everyday life (Bașibüyük & Șahin, 2019). Bütüner and Baki (2020) stated that students' beliefs about Mathematics can be increased by applying HoM in Mathematics classes through fun, useful and interesting class activities. In addition, the usage of HoM also helps students to develop meaningful relationships between abstract mathematical ideas and practical applications in real-world contexts (Bailey, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The world over the importance and role of HOM in mathematics education is acknowledged by international professional councils such as the National Council of Teachers of Mathematics (NCTM) in the United States of America. Research in mathematics education affirms the centrality of HOM (Bütüner & Baki, 2020;Furinghetti, 2000;Goktepe & Ozdemir, 2013;Horton & Panasuk, 2013;Siu, 2004). Key findings in this scholarly work point to the utility of HOM in learner mathematics-schema development; its capacity in providing for open-mindedness and flexibility in resolving mathematical problems (Furinghetti, 2000).…”
Section: Literature Reviewmentioning
confidence: 95%
“…This concept of history of mathematics was defined by this study as the adoption of history of mathematics activities (or as a pedagogical tool) in teaching a mathematics course, to enable students to recognize the dynamic and developing nature of mathematics, to deepen their perceptions of successful mathematicians, to show them how and why mathematics emerged, and help them to enjoy the mathematics course by experiencing the fun and interesting side of it (Butuner & Baki, 2020). The use of the history of mathematics has been accepted by many researchers in mathematics classes (Baki & Gursoy, 2018).…”
Section: History Of Mathematics and Students' Interest In Mathematicsmentioning
confidence: 99%